Replication of an Evaluation of Teacher Training in the Classification of Programming Exercises Using Bloom's Taxonomy - Masapanta-Carrion, Susana; Velazquez-Iturbide, J. Angel (IEEE Global Engineering Education Conference, 2022)
Repositories are a key resource for instructors and students interested in accessing high-quality exercises for either formative or summative assessment. One central concern in the design of repositories is the classification of exercises, which is typically based on a number of criteria. One common criterion in computing education is Bloom taxonomy, which is frequently used to develop and classify assessment tasks. However, the existing literature reports on educators' difficulties and divergences in the classification of assessment tasks based on Bloom's taxonomy. The paper makes two proposals aimed at enhancing computing educators' training in Bloom's taxonomy: classification of an exercise into several cognitive processes, and provision of computing examples. These recommendations could be used for education in any field of study by using examples specific to the field. Moreover, the paper presents the result of replicating an evaluation of the effect of these recommendations on computing educators. Some results were positive; for instance, decomposing the process to solve a task into several cognitive activities was natural to educators. However, high variation and low accuracy in educators' classifications persisted. Some lessons were learnt: the period of training should be longer, based on more examples and with more active training activities.